A systematic review of movement monitoring devices to aid the prediction of pressure ulcers in at‐risk adults. Issue 2 (30th July 2022) - Moore, Zena; Avsar, Pinar; O'Connor, Tom; Budri, Aglecia; Bader, Dan L.; Worsley, Peter; Caggiari, Silvia; Patton, Declan
Abstract: The present study sought to explore the impact of movement monitoring devices on risk prediction and prevention of pressure ulcers (PU) among adults. Using systematic review methodology, we included original research studies using a prospective design, written in English, assessing adult patients' movement in bed, using a movement monitoring device. The search was conducted in March 2021, using PubMed, CINAHL, Scopus, Cochrane, and EMBASE databases, and returned 1537 records, of which 25 met the inclusion criteria. Data were extracted using a pre‐designed extraction tool and quality appraisal was undertaken using the evidence‐based librarianship (EBL). In total, 19 different movement monitoring devices were used in the studies, using a range of physical sensing principles. The studies focused on quantifying the number and types of movements. In four studies the authors compared the monitoring system with PU risk assessment tools, with a variety of high and low correlations observed. Four studies compared the relationship between movement magnitude and frequency and the development of PUs, with variability in results also identified. Two of these studies showed, as expected, that those who made less movements developed more PU; however, the two studies also unexpectedly found that PUs occurred in both low movers and high movers. In the final two studies, the authors focused on the concordance with recommended repositioning based on the results of the monitoring device. Overall, concordance with repositioning increased with the use of a monitoring device. The synthesis of the literature surrounding bed monitoring technologies for PU risk prediction showed that a range of physical sensors can be used to detect the frequency of movement. Clinical studies showed some correlation between parameters of movement and PU risk/incidence, although the heterogeneity of approaches limits generalisable recommendations.